COMPARATIVE IN VITRO STUDY OF FOUR DENTAL MATERIALS USED IN RETROGRADE APICAL FILLING - Flores, Jorge Abel; Post, Letícia Kirst; Costa, Aline Tempel; Weber, João Batista Blessmann; Oliveira, Marília Gerhardt de (Archives of Oral Research, 2006)
OBJECTIVES: The objectives of this study were to evaluate the apical sealing ability of four dental materials used in retrograde fillings. MATERIAL AND METHODS: Eighty human maxillary canines were selected and treated endodontically. The apical ends were sectioned and root-end cavities were prepared. The sample was randomly divided in four groups of 20 specimens each. In each group, root-end cavities were filled with one of the following materials: ethyl cyanoacrylate (EC); silver zinc freea amalgam (AM); resin-modified glass-ionomer cement (GIC); or resin-modified glass-ionomer cement and light curing (GIC+light). Specimens were immersed in 0.2% methylene blue for 24 hours at 37° C and then sectioned longitudinally. The analysis of dye penetration was conducted by means of visual inspection of the buccal and lingual sections of the roots. RESULTS: Analysis of variance was used to compare results. The least marginal leakage was found in the EC group, followed by the GIC+light, GIC and AM groups, which had the greatest leakage. CONCLUSION: In the conditions of this work, the use of GIC+light and EC provided the best apical sealing.